Fail and guard : an interactive public art inquiry into the underlying attitudes towards socio-economic discrepancies in Stellenbosch - Salzwedel, Heidi (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.